oBike offers bicycle sharing services for UMPians - Siti Sarah, Mohamad Rajimi (2017)
Kuala Lumpur, 26 October – Universiti Malaysia Pahang (UMP) and oBike, a renowned bicycle sharing company championing the in-campus bicycle initiative, signed a Memorandum of Agreement (MoA) at the oBike Malaysia Sdn Bhd headquarters at Mid Valley, Kuala Lumpur recently. Through this agreement, about 1,200 bicycles will be available for usage at both UMP Gambang and Pekan campus.